2020
DOI: 10.3389/fnins.2020.00602
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Differences in the Gray Matter Volume and Functional Connections of the Amygdala Are Associated With Clinical Manifestations of Alzheimer’s Disease

Abstract: Objective Asymmetry is a subtle but pervasive aspect of the human brain, which may be altered in several neuropsychiatric conditions. Magnetic resonance imaging (MRI) studies have reported that cerebral structural asymmetries are altered in Alzheimer’s disease (AD), but most of these studies were conducted at the region-of-interest level. At the functional level, there are few reports of resting-state functional asymmetries based on functional MRI. In this study, we investigated lateral difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…In the present study, the cortical reductions were sometimes observed only in 1 hemisphere. The prevalence of asymmetrical cerebral alterations has been extensively documented in the brains of patients with AD ( 52 ), schizophrenia ( 53 ), autism ( 54 ), anxiety disorders ( 55 ), or even type II diabetes ( 56 ). In the present study, GMV was reduced in the right temporal lobe of patients with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the cortical reductions were sometimes observed only in 1 hemisphere. The prevalence of asymmetrical cerebral alterations has been extensively documented in the brains of patients with AD ( 52 ), schizophrenia ( 53 ), autism ( 54 ), anxiety disorders ( 55 ), or even type II diabetes ( 56 ). In the present study, GMV was reduced in the right temporal lobe of patients with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…This results in 152 MRI features (49 sums, 49 differences, 49 ratios, and 5 unpaired features). Brain asymmetry was previously associated with AD [47][48][49][50]. Equation 2 shows that differences were calculated by subtracting the right from the left volume similar to [48], where the cortical thickness was used instead of volumetric features…”
Section: Mri Feature Extractionmentioning
confidence: 99%
“…Those features describe the asymmetry of both hemispheres. Brain asymmetry measurements were associated with AD [47][48][49][50] and were also successfully applied for ML models in this field [75].…”
Section: Feature Selectionmentioning
confidence: 99%
“…This results in 152 MRI features (49 sums, 49 differences, 49 ratios, and five unpaired features). Brain asymmetry was previously associated with AD [47][48][49][50]. Equation 2 shows that differences were calculated by subtracting the right from the left volume similar to [48], where the cortical thickness was used instead of volumetric features.…”
Section: Mri Feature Extractionmentioning
confidence: 99%